2022
DOI: 10.1002/jmri.28318
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Differences of Cortical Topology Across the Adult Lifespan: Evidence From a Multisite MRI Study With 1427 Individuals

Abstract: Background Healthy aging is usually accompanied by alterations in brain network architecture, influencing information processing and cognitive performance. However, age‐associated coordination patterns of morphological networks and cognitive variation are not well understood. Purpose To investigate the age‐related differences of cortical topology in morphological brain networks from multiple perspectives. Study Type Prospective, observational multisite study. Population A total of 1427 healthy participants (59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This is consistent with previous studies of single‐subject morphological brain networks based on gray matter volume, which found a negative correlation for clustering coefficient and local efficiency with age (Kong et al, 2015 ; Shigemoto et al, 2023 ). However, using the same method as this work, a recent study found that clustering coefficient of CT networks showed an inverted U‐shaped age‐related trajectory (Wang et al, 2022 ). This discrepancy may be due to differences between the current study and previous one in the statistical model used (linear, quadratic, and cubic vs. quadratic) and/or in the data homogeneity with respect to site (single vs. multiple) and field strength (3 T vs. 1.5/3 T).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is consistent with previous studies of single‐subject morphological brain networks based on gray matter volume, which found a negative correlation for clustering coefficient and local efficiency with age (Kong et al, 2015 ; Shigemoto et al, 2023 ). However, using the same method as this work, a recent study found that clustering coefficient of CT networks showed an inverted U‐shaped age‐related trajectory (Wang et al, 2022 ). This discrepancy may be due to differences between the current study and previous one in the statistical model used (linear, quadratic, and cubic vs. quadratic) and/or in the data homogeneity with respect to site (single vs. multiple) and field strength (3 T vs. 1.5/3 T).…”
Section: Discussionmentioning
confidence: 94%
“…Using the newly developed approaches, two previous studies have explored early cortical development of the neonatal brain (Fenchel et al, 2020 ; Galdi et al, 2020 ). More recently, two large sample studies further examined single‐subject morphological brain networks across the adult lifespan (Shigemoto et al, 2023 ; Wang et al, 2022 ). However, these studies constructed single‐subject morphological brain networks either based on a single morphological feature (i.e., gray matter volume) or by integrating multiple features into a single model.…”
Section: Introductionmentioning
confidence: 99%
“…Aging in healthy populations is also commonly accompanied by changes in brain network topologies, leading to decreased information processing and cognitive performance. By exploring the trajectory of changes in cortical topology throughout the life cycle, Wang et al 45 confirmed the age‐related morphological network reconfiguration, and the findings may have implications for understanding age‐associated cognitive decline and for developing interventions to support healthy brain aging.…”
Section: Applications In the Human Brainmentioning
confidence: 90%
“…Thus, a sparsity threshold 0.25 < S < 0.49 with an interval of 0.015 was applied to binarize adjacency networks in the theoretical analysis graph. Previous studies had found that a measure of the graph‐theoretical network was able to reveal developmental changes in the functional organization in patients with age‐related hearing loss (Wang et al, 2022; Yong et al, 2022). We therefore focused on the measures of global network parameters of small‐world: L$$ L $$ (characteristic path length), C$$ C $$ (clustering coefficient), γ$$ \gamma $$ (normalized clustering coefficient), λ$$ \lambda $$ (normalized characteristic path length), δ$$ \delta $$ (small‐worldness) and the network efficiency parameters including Eg$$ {E}_g $$ (global efficiency) and El$$ {E}_l $$ (local efficiency) to characterize the global topological structure.…”
Section: Data Preprocessingmentioning
confidence: 99%